Gender Equality and the Sedekah Bumi Tradition: A Study of the Karangjong Village Community in Blora Regency - Tamara, Rinda Ocik; Sari, Ramadhanita Mustika (Universitas Tanjungpura, 2024)
This study aims to analyze the community's perception of gender equality in social activities, with a focus on the *Sedekah Bumi* tradition in Karangjong Village, Ngawen Subdistrict, Blora Regency. The research method used is a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The research participants consist of community members involved in the organization and participation of the *Sedekah Bumi* activities. The results show variations in perceptions of gender roles within the *Sedekah Bumi* tradition. While some believe that the tradition reflects traditional gender roles related to the division of labor based on sex, others observe a shift toward gender equality in participation and contributions to the event. These findings illustrate the complexity of gender dynamics within the context of traditional community activities, which in turn provides insights into the challenges and opportunities for achieving gender equality at the local level. This study contributes to understanding the interaction between local traditions and social change, particularly concerning gender issues.